The Role of Secretaries in Addressing Cyber Security Challenges in the Modern Workplace (Literature Study) - Perdana, Reza Feris (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The development of information technology has changed the way organizations work, shifting towards a modern, digitally-based work environment. This change has placed secretaries in a strategic position as managers of organizational information and communication, as well as guardians of data confidentiality. However, the increased use of digital technology has also been accompanied by an increase in cyber security threats such as phishing, malware, data leaks, and social engineering. This study aims to analyze the role of secretaries in facing cyber security challenges in modern work environments based on a literature review. The research method used is a qualitative approach with a literature study of scientific journals, academic books, and official reports from institutions related to information security and the secretarial profession. The results of the study show that secretaries have an important role in the organization's information security system because they are directly involved in the management of digital documents and leadership communication. The main challenges faced include limited digital security literacy, high workloads, and a lack of structured information security policies. Therefore, it is necessary to improve the competence of secretaries through cybersecurity training, the implementation of information security standard operating procedures, and the strengthening of a digital security culture within organizations. This research is expected to provide theoretical and practical contributions to the development of the secretarial profession in the digital era and serve as a reference for organizations in improving human resource-based information security systems.